2020
DOI: 10.3390/ijerph17103683
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-Related Knowledge, Attitudes, and Behaviors among Community-Dwellers at Risk for High Blood Pressure in Shanghai, China

Abstract: This study aimed to investigate the hypertension-related knowledge, attitudes, behaviors (KAB), and socio-demographic determinants among community-dwellers who were at risk for hypertension in Shanghai, China. A cross-sectional survey was conducted in a district of Shanghai in 2017 using multi-stage cluster sampling, including 611 participants who were at risk for hypertension. Questionnaires were used to investigate KAB regarding hypertension prevention. Multivariable logistic regression was performed to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(30 reference statements)
0
8
1
1
Order By: Relevance
“…According to our findings, demographic factors had no effect on aftermath results after receiving the intervention. It is contradictory to previous studies in which gender and age were found to influence acceptance and behavior [31,32]. However, a study conducted by Anyanti et al [28] had similar results to ours, finding no significant effect of age and gender on participants' knowledge, which is consistent with our study's findings.…”
Section: Discussioncontrasting
confidence: 64%
“…According to our findings, demographic factors had no effect on aftermath results after receiving the intervention. It is contradictory to previous studies in which gender and age were found to influence acceptance and behavior [31,32]. However, a study conducted by Anyanti et al [28] had similar results to ours, finding no significant effect of age and gender on participants' knowledge, which is consistent with our study's findings.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, based on the KAB (knowledge, attitude and behaviour) model, behaviours are influenced by knowledge and attitudes. 19 Developed as a health promotion model, the KAB model explains that a person's knowledge directly affects their attitude and indirectly affects behaviour through their attitude. 20 This study aimed to examine the different mediating effects of attitudes on behaviours and their mechanisms, providing information for the development of targeted health education interventions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In addition, based on the KAB (knowledge, attitude and behaviour) model, behaviours are influenced by knowledge and attitudes. 19 Developed as a health promotion model, the KAB model explains that a person’s knowledge directly affects their attitude and indirectly affects behaviour through their attitude. 20…”
mentioning
confidence: 99%
“…Sadeq and Lafta reported that among hypertensive patients attending hospitals in Baghdad, more than 60% had a good knowledge about hypertension [7]. Gong et al informed that the knowledge and belief of hypertension prevention were good in Shanghai [8]. Bashaar et al stated that the hypertension related knowledge among respondents was found to be good at community level in Kabul [9].…”
Section: Resultsmentioning
confidence: 99%